Three-phase photovoltaic grid inverter system design based on PIC24FJ256GB110 for distributed generation - Ihsan Jabbar Hasan; Nahla Abdul Jalil Salih; Nadhir Ibrahim Abdulkhaleq (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
In recent years, the demand for energy generated by photovoltaics has increased because of the cheapness of this energy, especially in the Middle East. This study focuses on the design and implementation of a three-phase photovoltaic inverter system for distribution of generator applications. The three-phase inverter used in this study was designed using GWM 100-01X1 as a three-phase full bridge MOSFET package. The MOSFET full bridge of the three-phase inverter is driven using IR2104 gate driver IC, and the Hall sensors of the voltage and current are used to measure the AC and DC voltage and current. The SPWM signal is generated using a PIC24FJ256GB110 as a microcontroller and interfaced to the full bridge package. Simulation and experimental results are presented to validate the three-phase inverter design.